PEMBELAJARAN BAHASA ARAB PADA AWAL PENERAPAN K-13 DI MADRASAH ALIYAH MATARAM – NTB - Nasarudin Nasarudin (Armala, 2020)
One of the compulsory subjects in madrasas in the 2013 curriculum is Arabic. Arabic as the subject of learning in KTSP is certainly different when it is in the 2013 curriculum. This is seen in the Core competencies, the core competencies of Arabic are the competencies that are expected to be possessed by students after learning Arabic as a standard competency for graduates. Achieving such competence is a hard task for a teacher because he is required to be able to characterize Arabic in students, especially Arabic only as a tool consisting of a series of skills, namely listening, speaking, reading and writing. So that in practice teachers are still carried away by the nuances of the previous curriculum and have not been able to make learning designs in tune with the characteristics of the 2013 Curriculum.